Analyzing Speech Acts of the Main Characters in All Quiet on the Western Front Movie Script - Risa Rismawati; Alek Andika; Hastri Firharmawan (Universitas Muria Kudus, 2026)
This study aims to analyze the speech acts used by the main characters in All Quiet on the Western Front movie script using the speech acts theory approach developed by John Langshaw Austin and John Searle. Speech acts in this context refer to the use of language as a tool to carry out communication actions, such as statements, requests, commands, and other expressions. This study identifies and classifies speech acts that appear in the form of locutionary, illocutionary, and perlocutionary acts, focusing on the speech acts revealed in the dialogues of the main characters in the movie script. In addition, illocutionary acts are further divided into five main categories, namely assertive, directive, commissive, expressive, and declarative, expressed by the main characters. The research method used is descriptive qualitative, which allows researchers to analyze data in depth from the movie script and examine how the main characters use language to convey their thoughts and feelings in facing various tense situations on the battlefield. The results of the study indicate that illocutionary speech acts, especially those containing commands and requests or directive illocutionary acts, have an important role in character development and the formation of atmosphere in the movie. This research is expected to provide deeper insight into how language contributes to building narratives and characters in war movie, as well as enriching pragmatic studies in speech acts theory.